2005
DOI: 10.1007/bf03166347
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic resonance studies of aniline oligomers formed in the reaction of aniline with 1,1-diphenyl-2-picrylhydrazyl

Abstract: Aniline oligomers, which are formed in the reaction of aniline with 1,1-diphenyl-2-picrylhydrazyl (DPPH) in methanol and chloroform as solvents, are investigated by means of magnetic resonance techniques. The electron paramagnetic resonance (EPR) spectrum of the products of the reaction of aniline with DPPH (mole ratio, 2:1) in chloroform solution, and of aniline with DPPH (mole ratio, 1:2) in methanol solution, were recorded as the reaction progressed, and after the reaction was finished. The spectra of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…3,[9][10][11][12][13][14] PANI and fPANIs are efficient radical scavengers for the stable R,R-diphenyl-β-picrylhydrazyl (DPPH) free radical. [15][16][17][18][19][20][21] The radical-scavenging property of PANI and fPANIs is beneficial for protection of foodstuffs against deterioration or rubber against oxidative aging and has significant implications for their inclusion as biomaterials in biological media. Wang et al showed that the antioxidant activity of PANI increased as the nanofibers' surface area increased.…”
Section: Introductionmentioning
confidence: 99%
“…3,[9][10][11][12][13][14] PANI and fPANIs are efficient radical scavengers for the stable R,R-diphenyl-β-picrylhydrazyl (DPPH) free radical. [15][16][17][18][19][20][21] The radical-scavenging property of PANI and fPANIs is beneficial for protection of foodstuffs against deterioration or rubber against oxidative aging and has significant implications for their inclusion as biomaterials in biological media. Wang et al showed that the antioxidant activity of PANI increased as the nanofibers' surface area increased.…”
Section: Introductionmentioning
confidence: 99%